2016
DOI: 10.1080/2000656x.2016.1175357
|View full text |Cite
|
Sign up to set email alerts
|

Smoking increases donor site complications in breast reconstruction with DIEP flap

Abstract: It was found that former smokers had a risk for donor site complication more than double that of never smokers (OR =2.12, CI =1.10-4.10, p = 0.025). Differences in BMI within the range from 18-33.7 did not have any significant impact on complication rates, neither at the donor site nor at the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…A comparison of subgroups differentiated according to their respective BMI category showed that being overweight (BMI 25 to ≤ 30 kg/m 2 ) or obese (BMI 30 to ≥ 40 kg/m 2 ) was associated with a higher incidence of flap-specific complications, particularly flap edge and fat necrosis (p < 0.05). Other studies have reported similar results [36,41,42].…”
Section: Discussionsupporting
confidence: 72%
“…A comparison of subgroups differentiated according to their respective BMI category showed that being overweight (BMI 25 to ≤ 30 kg/m 2 ) or obese (BMI 30 to ≥ 40 kg/m 2 ) was associated with a higher incidence of flap-specific complications, particularly flap edge and fat necrosis (p < 0.05). Other studies have reported similar results [36,41,42].…”
Section: Discussionsupporting
confidence: 72%
“…Better still, this particular study even suggests that obesity is negligible as an important risk factor in general surgery [ 51 ]. Studies by Modarressi et al, Chang et al, and Klasson et al achieved similar results: no significant association between obesity and donor-site complications was discovered [ 52 , 53 , 54 ]. In opposition to these findings, the meta-analysis by Schaverien et al determined a significant association between obesity and complications both at donor and recipient sites [ 12 ].…”
Section: Discussionmentioning
confidence: 69%
“…28 Smoking is associated with complications and unplanned reoperations in flap surgeries, with evidence supporting increased risk with higher doses and longer smoking history. [29][30][31][32][33][34] A large systematic review found a clear association between smoking tobacco and flap necrosis and a clear benefit of cessation for 1 week versus 24 hours preoperatively. 35 Another systematic review and metaanalysis has found that smoking has a negative impact on flap survival, including increased risk of hematoma and overall surgical complications.…”
Section: Perioperative Nicotine Replacement Therapy Detrimentsmentioning
confidence: 99%